Economic diversification of a mining town: a case study of Oranjemund - Helmuth, Angelo (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
Can mining industries and mining based localities promote Local Economic Development (LED)? This case study, on the mining town of Oranjemund, seeks to examine the economic diversification prospects of the town. Stakeholder views are considered and their aspirations determined, through an interview process. Relevant theories on economic development, growth and sustainability are outline. Lessons are drawn from local and international empirical studies on mining towns. The roles and contributions stakeholders and institutions could realize that could lead to local economic diversification and LED are defined. The opportunities and threats that could affect the town's LED process are identified. This paper concludes that it is imperative that sound relationships be developed amongst key stakeholders. It further, recommends that a strategic LED plan be designed for Oranjemund and that national government, through the regional and local authority, lead the process.
Keywords: Economic development -- Namibia -- Oranjemund -- Case studies; Mineral industries -- Namibia -- Oranjemund -- Case studies; Sustainable development -- Namibia -- Oranjemund